Role of Saccharomyces cerevisiae Fermentation in Enhancing Egg Protein Bioavailability and Storage Potential - Fadhila, Farah Rosyihana; Nuryanto, Nuryanto; Fitriyono Ayustaningwarno; Sonia Kurnia Dewi; Ninik Rustanti; Ani Margawati; Sugiharto (Universitas Airlangga, 2026)
Eggs are a rich source of high-quality protein and essential nutrients, but their limited shelf life and processing-induced nutrient loss pose challenges. Addressing these limitations through fermentation could enhance their nutritional and functional properties. This study aimed to address these limitations by exploring fermentation as a strategy to enhance the nutritional and functional properties of egg-based products. Specifically, the research investigated the effects of Saccharomyces cerevisiae fermentation on the nutritional value, protein digestibility, and shelf life of egg flour, to achieve this, liquid eggs were inoculated with S. cerevisiae and subjected to fermentation at 30°C for 48 hours. The fermented product was then dried at 50°C to obtain egg flour. Nutritional improvements were assessed through in vitro protein digestibility tests, while shelf life was evaluated using the Accelerated Shelf Life Testing (ASLT) method, applying the Arrhenius equation under different storage temperatures. Flour Liquid eggs were inoculated with fermipan and fermented at 30°C for 48 hours, followed by drying at 50°C to produce egg flour. In vitro protein digestibility was analyzed, and the Accelerated Shelf Life Testing (ASLT) method with the Arrhenius equation was used to estimate shelf life under varying storage conditions. Fermentation improved protein digestibility significantly, increasing from 42.60% in unfermented samples to 77.48%. Shelf life analysis showed that fermented egg flour had a stability of 30 days at 30°C, 24 days at 40°C, and 19 days at 50°C.